Effectiveness of Voytik-Harbin Protocol in Fabrication of Ram’s Testicular-Derived Hydrogel and Its Impact on Mouse In Vitro Spermatogenesis - Leila Rashki Ghaleno; Tohid Rezaei Topraggaleh; Leila Montazeri; Abdolhossein Shahverdi; Mojtaba Rezazadeh Valojerdi (International Journal of Fertility and Sterility)
Background: The utilization of decellularized extracellular matrix (dECM) derived from animal testis tissue hasdemonstrated potential as a component of tissue-specific scaffolds. Current research is mostly centered arounddECM as a natural resource for culturing testicular cells. This study aimed to assess firstly the comparison ofVoytik-Harbin (VH) and Frytes protocol in creating Ram’s dECM testis hydrogel and secondly the evaluation ofthe best protocol effect on in vitro spermatogenesis.Materials and Methods: In this experimental study, the six testes of mature rams were decellularized and the hydrogelproduction was performed by i. The Frytes protocol utilized a concentration of 1 mg/mL of pepsin, dissolvedin either 0.1 or 0.01 M HCl, and ii. The VH protocol was involved 10 mg of pepsin per 100 mg of ECM in 0.5 M ofacetic acid. Subsequently, mouse testicular cells were cultivated on collagen hydrogel as the control and the moreeffective testicular-derived hydrogel (TDH) to evaluate the early stages of in vitro spermatogenesis.Results: While the Freytes protocol produced a homogeneous pre-gel solution with both HCl concentrations; elevatingthe pH to 7.4 loosened the hydrogel and made gelation problematic. In contrast, the VH protocol solidifiedthe hydrogel and produced a strong hydrogel due to its gelation consistency. Furthermore, the prepared hydrogel byVH with 25 mg of dECM had a significantly higher priority in terms of rheology and structure (P<0.05). Followingmouse testicular cell culture, TDH and collagen hydrogel did not differ significantly in terms of cell survival ratesand the mRNA expression of early spermatogenesis genes.Conclusion: Using the VH protocol for producing ram TDH resulted in a firm hydrogel with a high frequency ofrepeat, which may be suited for testicular cell growth.